Probing and manipulating the Mexican hat-shaped valence band of In2Se3 - James Felton; Jordan Harknett; Joe Page; Zhuo Yang; Nada Alghofaili; James N. O’Shea; Laurence Eaves; Yoshimitsu Kohama; Mark T. Greenaway; Amalia Patanè (Nature Communications)
Abstract Ferroelectrics based on van der Waals semiconductors represent an emergent class of materials for disruptive technologies ranging from neuromorphic computing to low-power electronics. However, many theoretical predictions of their electronic properties have yet to be confirmed experimentally and exploited. Here, we use nanoscale angle-resolved photoemission electron spectroscopy and optical transmission in high magnetic fields to reveal the electronic band structure of the van der Waals ferroelectric indium selenide (α-In2Se3). This indirect bandgap semiconductor features a weakly dispersed valence band, which is shaped like an inverted Mexican hat. Its form changes following an irreversible structural phase transition of α-In2Se3 into β-In2Se3 via a thermal annealing in ultra-high vacuum. Density functional theory supports the experiments and reveals the critical contribution of spin orbit coupling to the form of the valence band. The measured band structure and its in situ manipulation offer opportunities for precise engineering of ferroelectrics and their functional properties beyond traditional semiconducting systems.